The views of postnatal women and midwives on midwives providing contraceptive advice and methods: a mixed method concurrent study - Susan H. Walker; Claire Hooks; Diane Blake (BMC, 2021)
Abstract Background Provision of contraception to women in the immediate postnatal period has been endorsed by professional bodies, to reduce the incidence of short inter-pregnancy intervals. This study examined the views of postnatal women and practising midwives regarding provision of contraceptive advice and contraceptive methods by midwives, in a region of the United Kingdom. Methods A mixed-method approach using qualitative interviews with midwives, and a postnatal survey followed by qualitative interviews with postnatal women, in five hospitals in the East of England. Twenty-one practising midwives and ten women were interviewed. Two hundred and twenty-seven women returned a survey. Survey data was analysed descriptively, augmented by Student's t-tests and Chi-squared tests to examine associations within the data. Interviews were recorded, transcribed and analysed guided by the phases of thematic analysis. Results Midwives and women supported the concept of increased midwifery provision of contraceptive advice, and provision of contraceptive methods in the postnatal period. Convenience and an established trusting relationship were reasons for preferring midwifery provision over visiting a doctor for contraception. The best time for detailed discussion was reported to be antenatal and community visits. The Progesterone-only-pill (POP) was the method, in which women indicated most interest postnatally. Concerns for midwives included the need for increased education on contraceptive methods and training in supplying these. Structural barriers to such provision were time pressures, low prioritisation of contraceptive training and disputes over funding. Conclusions Women reported interest in midwives supplying contraceptive methods and expressed the view that this would be convenient and highly acceptable. Midwives are supportive of the concept of providing enhanced contraceptive advice and methods to women in their care, and believe that it would be advantageous for women. Institutional support is required to overcome structural barriers such as poor access to continuous professional development, and to allow contraceptive provision to be fully recognised as integral to the midwifery role, rather than a marginalised addition.